Effects of different dexmedetomidine doses on haemodynamic variability during laryngoscopy and intubation: A randomized double-blind study - Kalyani; Savita Meena; Siddharth Sharma (Journal of Applied Pharmaceutical Research, 2023)
Background: Effective airway management is vital in anesthesiology for preserving patient lives. Laryngoscopy and endotracheal intubation, commonly used procedures, can lead to undesirable outcomes due to vagal activation and sympathoadrenal reaction. This double-blind, randomized interventional study aimed to assess the impact of two different doses of dexmedetomidine on heart rate and blood pressure during laryngoscopy and intubation, which often induce tachycardia and hypertension, particularly risky for patients with hypertension, myocardial insufficiency, and cerebrovascular disease. Methods: Seventy-six participants, aged 20-60 years and classified as American Society of Anesthesiologists (ASA) Grade I & II, were enrolled after Institutional Ethics Committee approval. Random allocation assigned them to two groups: Group A (0.5 µg/kg dexmedetomidine) and Group B (1.0 µg/kg dexmedetomidine) before anesthesia induction. Hemodynamic measurements were recorded at various time points: pre- and post-drug administration, before intubation, and at intervals thereafter. Results: Both groups exhibited similar age, weight, and gender distribution. Group B consistently demonstrated lower hemodynamic variables compared to Group A after laryngoscopy and intubation. Additionally, Group B required a smaller induction dose of propofol than Group A. No significant adverse effects were reported in either group during the study. Conclusion: The study suggests that intravenous administration of dexmedetomidine at a rate of 1 µg/kg is more effective than 0.5 µg/kg in attenuating the physiological response to laryngoscopy and intubation. Moreover, it reduces the required propofol dose for anesthesia induction. These findings highlight the potential benefits of higher dexmedetomidine doses in mitigating adverse physiological effects during airway management procedures